Molecular Characterization of ESBL Producing Klebsiella Species Isolated from Several Major Hospitals in Iran - Ghafourian, Sobhan (2011)
Extended Sepectrum beta-lactamas have been found in a wide range of Gram-negative rods. However, the vast majority of strains expressing these enzymes belong to the Enterobacteriaceae family. K.pneumoniae remains as the major ESBL producer. The strong selective pressure for the use of beta-lactam drugs exerted on ESBL producer strains may lead to the selection of strains that hyper produce ESBLs. The plasmids that harbor genes encoding ESBLs frequently contain other genes encoding mechanisms of resistance to aminoglycoside and cotrimoxazole. Over the last two decades, the incidence of infections caused by multidrug-resistant Klebsiella strains has increased. Extended spectrum beta-lactamase enzymes were first described in K. pneumoniae isolates in 1983 in Europe. The focus of this study was To determine epidemiology of ESBL-producing K. pneumoniae and K. oxytoca in Iran during different seasons, To identify the prevalence of ESBLs producing K. pneumoniae and K. oxytoca in Iran during different seasons. To determine the prevalence of blaTEM, SHV and CTX-M responsible for ESBL production among ESBL-producing K. pneumoniae and K. oxytoca in the different wards and hospitals in Iran. To investigate the susceptibility of K. pneumoniae and K. oxytoca producing ESBLs towards non beta- lactam antibiotics. To identify the various clonal types of ESBL-producing K. pneumoniae in Milad hospital. To detect the dominant ESBL clonal types. Six hundred and seven Klebsiella spp were identified during the period March 2007 to April 2008 in three hospitals in three cities (Ilam, Tabriz and Tehran) in Iran. The strains were isolated from urinary tract infections, Intensive care units, surgery wards, lesion infections and Respiratory tract infections. ESBLs were identified by phenotypic and genotypic methods. Klebsiella spp producing ESBLs were evaluated against non beta- lactam antibiotics. MLST was performed for dissemination of ESBL producing K. pneumoniae. Of the six hundred and seven Klebsiella spp isolated from the three hospitals, 34.26%, 16.96% and 43.65% K. pneumoniae were obtained from Ilam, Emam Reza and Milad hospitals, respectively. Further, 1.98%, 0.66% and 2.47% Klebsiella oxytoca were also obtained from Ilam, Emam Reza and Milad hospitals, respectively. The findings in this study revealed that 36.5%, 51.7% and 45.6% of K.pneumoniae were producing ESBLs in Ilam, Milad and Emam Reza hospitals, respectively. The highest ESBLs production of K.pneumoniae observed in winter in RTI (54.5%). As for K.oxytoca it showed that 25%, 73.3% and 75% of the isolates were positive for ESBLs production in Ilam, Milad and Emam Reza hospitals, respectively. The most K.oxytoca and ESBLs producing K.oxytoca recurred in winter. Resistance towards non-beta-lactam antibiotics in K. oxytoca was only observed in Milad hospital and found in cotrimoxazol and amikacin. In Ilam hospital, of the seventy-six K.pneumoniae producing ESBLs, 9.21% were resistant to amikacin, 3.94% to ciprofloxacin and 11.74%, to cotrimoxazol. Of the one hundred and thirty seven K.pneumoniae producing ESBLs in Milad hospital, 35.8%, 21.2% and 38.7% of them were resistant to amikacin, ciprofloxacin and cotrimoxazol, respectively. Resistance toward all the antibiotic in this study in cold seasons was more than the other seasons. In Emam Reza hospital, 21.2%, 4.25%, 21.2% and 0% of K.pneumoniae producing ESBLs showed resistance to amikacin, ciprofloxacin, cotrimoxazol and imipenem, respectively. In all the K.oxytoca, blaSHV was responsible for the production of ESBLs. Thirty-five blaTEM, two hundred and eighteen blaSHV and fifty-six blaCTX-M were responsible for ESBLs production in K.pneumonae. The analysis showed significant difference of ESBLs production by K.pneumoniae in winter (53%) in comparison to the other seasons with P ≤ 0.01. K.pneumoniae producing ESBLs more detected in RTI with P ≤ 0.03.The results also showed significance different in to blaSHV that was dominant gene responsible for ESBLs production P ≤ 0.049 but no significant difference observed in blaTEM and blaSHV. Based on the nucleotide variations of the five selected genetic loci, twenty-five different STs could be identified among thirty K.pneumoniae producing ESBLs isolates. The most frequently encountered were ST14 (four isolates) ST16 (two isolates) and ST18 (two isolates). Six colonal complexes were also identified. This study, conducted in different seasons and on different wards, is the first of its kind in the world. The prevalence of ESBLs among clinical isolates varied in different hospital in Iran, the highest prevalence was observed in Milad hospitals (51.6%) follow by Emam Reza (43.7%) and Ilam hospitals (36.5%). Generally, the findings released more prevalence of ESBLs production in Iran. The results showed that the highest ESBLs production was found in K.oxytoca isolated from patients in Emam Reza Hospital, Tabriz, and the lowest frequency of ESBLs production was found in K.oxytoca in Ilam hospital. BlaSHV was found as dominant gene responsible for ESBLs production by K. pneumoniae and K.oxytoca and followed by blaCTX-M.Different clonal complex and St obtained. CC1 and ST14 were found as a dominant CC and ST, respectively. ESBL-producing isolates in this study were found to be concomitantly resistant to various antibiotic classes, indicating the co-transfer of a range of genes accounting for resistance to these antibiotics. Therefore, therapeutic choices became limited in our hospital. Based on our in vitro findings, imipenem was the most effective antibiotic against ESBL-producing K. pneumoniae , followed by Ciprofloxacine. Key Words: ESBLs, Klebsiella spp, MLST, Iran